Prescribed performance synchronization of complex dynamical networks with event-based communication protocols - Fan, Aili; Li, Junmin (Information sciences, 2021)
The paper addresses the prescribed performance synchronization (PPS) issue for complex dynamical networks (CDNs) using an event-triggered communication mechanism and PPS scheme with event-based protocols is designed for the CDNs. The designed synchronization control strategy can reduce the overshoot in transient processes, and stabilize synchronous errors at the origin. Furthermore, by introducing event-based protocols, continuous communication of the networks is avoided, so that the frequency of information communication is reduced and network resources are saved. Moreover, Zeno behavior in the networks can be excluded. Combining the Lyapunov stability method, a sufficient condition for asymptotic synchronization is proposed. Finally, the validity of the results is demonstrated by the CDNs with one link pendulum and Chua’s chaotic circuit (CCC) systems.